REFLECTIVE THINKING CHARACTERISTICS: A STUDY IN THE PROFICIENT MATHEMATICS PROSPECTIVE TEACHERS - Cholis Sa'dijah; Muhammad Noor Kholid; Erry Hidayanto; Hendro Permadi (IKIP Siliwangi and I-MES, 2020)
Reflective thinking begins with repeated confusion and evaluation to solve a problem. There are four aspects to reflective thinking, namely techniques, monitoring, insight, and conceptualization. However, the problem-solvers’ reflective thinking characteristics in mathematical problems have not been discovered. The study describes the reflective thinking characteristics of proficient mathematics prospective teachers based on four aspects. The qualitative research was conducted at Universitas Muhammadiyah Surakarta with a total of 64 reflective thinkers. Data collected by test, observation sheets, and interview methods. The tests were administered twice. The instruments developed has been through the validation process and declared valid. Data analyzed through the stages of reduction, presentation, and verification. We successfully conclude that proficient mathematics prospective teachers have complete and consistent reflective thinking characteristics. Further research can be focused on the characteristics of reflective thinking based on another aspect.